2019
DOI: 10.1080/21501203.2019.1635217
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the subgenusEumitriain Tanzania

Abstract: Several Usnea species in subgenus Eumitria (Parmeliaceae, lichenized Ascomycota) have been described from East Africa in the past decades. These have been based on morphology and chemistry data while molecular studies remain very limited. In this paper we are for the first time publishing phylogenetic analyses along with morphological and chemical data for Eumitria. A total of 62 new sequences of Eumitria (26 ITS, 20 nuLSU, 6 MCM7, 10 RPB1) were generated in this study. nuLSU, MCM7 and RPB1 sequences are here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…1 or as Usnea lineage 14A in the corresponding publication, i.e., denoting specific taxa without a formal name awaiting further work (Wirtz et al 2006;Gerlach et al 2019aGerlach et al , 2020. In three cases (MF669881, MF669883, MN080241), the full identification provided in the publication deviated from that of the GenBank accession (Gerlach et al 2019a;Temu et al 2019). For 65 accessions, the labels given in the principal components of the published work (voucher specimens, phylogenetic trees) differed from those submitted with the accessions.…”
Section: Categorymentioning
confidence: 98%
See 2 more Smart Citations
“…1 or as Usnea lineage 14A in the corresponding publication, i.e., denoting specific taxa without a formal name awaiting further work (Wirtz et al 2006;Gerlach et al 2019aGerlach et al , 2020. In three cases (MF669881, MF669883, MN080241), the full identification provided in the publication deviated from that of the GenBank accession (Gerlach et al 2019a;Temu et al 2019). For 65 accessions, the labels given in the principal components of the published work (voucher specimens, phylogenetic trees) differed from those submitted with the accessions.…”
Section: Categorymentioning
confidence: 98%
“…is one of the largest genuslevel clades of lichenized fungi, currently listed among the ten most speciose genera, with approximately 350 taxa (Thell et al 2012;Lücking et al 2017a). The classification of usneoid lichens has been in flux, besides Protousnea (Motyka) Krog either recognizing a single genus Usnea s.lat., with several subgenera and sections (Motyka 1936(Motyka , 1938Ohmura 2002;Ohmura & Kanda 2004;Wirtz et al 2006;Truong & Clerc 2013;Ohmura & Kashiwadani 2018;Temu et al 2019) or separating Dolichousnea (Y. Ohmura) Articus, Eumitria Stirt., and Neuropogon Nees & Flot. (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a detailed analysis of all available ITS barcoding data for this hyperdiverse genus (in the definition by Lücking et al 2017a), Lücking et al (2020c) demonstrated numerous shortcomings in sequence data pertaining to Usnea: first and foremost taxonomic and geographic gaps, but also substantial issues with sequence identifications and voucher information. In addition, species identification in Usnea is challenging, as many presumably widespread taxa represent complexes of partly unrelated lineages and much work remains to be done to fully resolve the taxonomy of this genus (Seymour et al 2007;Wirtz et al 2008Wirtz et al , 2012Lumbsch & Wirtz 2011;Saag et al 2011;Shen et al 2012;Truong & Clerc 2012Truong et al 2013a, b;Clerc 2016;Mark et al 2016;Gerlach et al 2017Gerlach et al , 2019Gerlach et al , 2020Clerc & Otte 2018;Grewe et al 2018;Lagostina et al 2018;Dorey et al 2019;Temu et al 2019;Lücking et al 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…However, he has also contributed to other topics in his active life as a researcher (Fig. 3), including: lichen conservation in Switzerland and the red-list (e.g., Vust et al 2015), lichen inventory (e.g., Habashi & Clerc 2012, 2013a, chemistry (e.g., Gadea et al 2019), molecular biology (Armaleo & Clerc 1991, 1995Döring et al 2000;Truong et al 2013;Divakar et al 2015;Gerlach et al 2018;Temu et al 2019;Jung et al 2019), the taxonomy in genera other than Usnea (e.g., Botryolepraria Canals et al, Candelariella Müll. Arg., Melanohalea O. Blanco et al, Melaspilea Nyl., Menegazzia A.…”
mentioning
confidence: 99%